Degenerative Ataxic Disorders - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1987)
Harding AE at the Institute of Neurology, London, author of the Hereditary Ataxias and Related Disorders (Edinburgh, Churchill Livingstone, 1984) reviews the classification, causes, clinical characteristics and treatment of degenerative ataxias.